Enhanced green upconversion luminescence in tetrahedral LiYF4:Yb/Er nanoparticles by manganese(ii)-doping: the key role of the host lattice. Issue 6 (24th January 2018) - Zhou, Bin; Xu, Bing; He, Huimei; Gu, Zhanjun; Tang, Bing; Ma, Ying; Zhai, Tianyou
Abstract : We highlight enhanced green upconversion luminescence in tetrahedral LiYF4 :Yb/Er nanoparticles by manganese(ii )-doping and the key role of the host lattice. Abstract : We report the enhancement of green upconversion luminescence in tetrahedral LiYF4 :Yb/Er nanoparticles by Mn 2+ ion doping, which is different from the enhanced single-band red emission dominated by Mn 2+ ions in cubic NaLnF4 :Yb/Er (Ln = Y, Gd, Lu) nanoparticles. The energy levels of the first excited state 4 T1 of Mn 2+ in tetrahedral LiYF4 :Gd and cubic NaGd(Y)F4 are compared by detection of emissions from Mn 2+ via the energy transition from Gd 3+ to Mn 2+ with excitation at 275 nm. The coordination environments of Mn 2+ in these two host lattices have been investigated by X-ray absorption fine structure measurements. The results demonstrate that the formation of tetrahedral MnF4 in tetragonal LiYF4 arising from the replacement of Ln 3+ ions with Mn 2+ ions leads to a higher energy level of the Mn 2+ 4 T1 state than that in octahedral MnF6 in cubic NaYF4 . The high-lying excited state of tetrahedral MnF4 is close to the green emitting 4 S3/2 state of Er 3+ and thus enhances green upconversion emission in tetragonal LiYF4 :Yb/Er, while the low-lying excited state of octahedral MnF6 dominates red emission in cubic NaYF4 :Yb/Er. These findings provide direct evidence for the key roles of the host lattices and more possibilities in modulating the upconversion behaviour of lanthanide-based nanoparticles by transition-metal ion doping to achieve the desired goals of specific applications.